Peran Keluarga dalam Pembelajaran Agama Islam Anak Usia Dini di KB Ar Raudhah Kisaran - Panjaitan, Raudhah; Rahman, Mhd. Habibu (Medan Resource Center, 2025)
This study investigates the role of families, particularly parents, in supporting Islamic religious education for early childhood at Ar Raudhah Kindergarten in Kisaran. Using a descriptive qualitative method with a case study approach, data were collected through interviews, observations, and documentation involving eight parents of students enrolled at the school. The findings reveal that parents demonstrate a strong commitment to religious education by consistently modeling worship practices, facilitating religious discussions at home, and actively engaging in school-based religious programs. A unique insight from this study is the emergence of home-based collaborative religious routines, such as shared Qur’an reading sessions and family prayer schedules, which reinforce the teachings from school in a familial context. Additionally, the research highlights the presence of mutual reinforcement between the family and the institution, enabling a more holistic and continuous religious learning experience. This dynamic collaboration underscores the pivotal role families play in shaping children’s spiritual foundations from an early age.